La meta cognición y los procesos de lectura. - JÁCOME SOTO, Mayra Elizabeth (2019)
Reading processes and their relationship with metacognition have become a topic of great importance within the educational system. Therefore, this research seeks to generate a high impact with the application of reading processes that allow reaching metacognition, which is important in terms of its usefulness and management in the teaching-learning process in order to understand their own knowledge by students. The purpose of this study was to diagnose the impact of the implementation of reading processes and the appropiation of their knowledge to reach metacognition. This study has been developed by following the students the sixth grade students of General Basic Education at Quito Sur Fiscal Education Unit. This research was based on the quantitative approach by using the, inductive, deductive, method, which will allow to carry general definitions about reading processes and how to reach metacognition up to particular aspects. In addition, the information sheet has been used as a research for gathering information, using the survey as fundamental elements for the detection of the problem. The main problem detected in the diagnostic phase is the lack of motivation of the students to perform the reading since they have not acquired reading processes and they have not reached metacognition, either. The purpose of this study was to promote the diagnosis of reading processes and how to arrive at metacognition so that future researchers generate strategies that let students to appropriate their knowledge. It mean show to know their own ways of acquiring knowledge.